2021
DOI: 10.21037/tlcr-20-1056
|View full text |Cite
|
Sign up to set email alerts
|

An immune-related gene expression signature predicts brain metastasis in lung adenocarcinoma patients after surgery: gene expression profile and immunohistochemical analyses

Abstract: Background: Lung adenocarcinoma (LUAD) with brain metastasis (BM) occurs frequently and has a poor prognosis. In this study, we aimed to assess the correlation between gene expression signatures and the development of BM after surgical resection of LUAD.Methods: We analyzed the immune-related gene expression profiles of 72 LUADs with and without BM after surgery and verified them using NanoString method and immunohistochemistry (IHC). We matched the Tumor, Node, Metastasis (TNM) stage in the groups with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Based on this, we predict that the physical features define largely the types of metastasizing cells can go through the BBBs to reach the internal parts of a brain and the enzymes may define the characteristics of primary cancer cells that survive and thrive in the brain microenvironment. Compared with published studies on prediction of brain metastasis for primary tumors, our model shows higher or comparable accuracy ( 56 , 57 ), but has two key superiorities: (i) the features used in our model are strongly supported by published studies and provide strong information about the key mechanisms of brain metastasis; and (ii) the primary locations of BMPs are not limited to one organ instead any organs, strongly suggesting that our predicted mechanism captures something fundamental.…”
Section: Resultsmentioning
confidence: 58%
“…Based on this, we predict that the physical features define largely the types of metastasizing cells can go through the BBBs to reach the internal parts of a brain and the enzymes may define the characteristics of primary cancer cells that survive and thrive in the brain microenvironment. Compared with published studies on prediction of brain metastasis for primary tumors, our model shows higher or comparable accuracy ( 56 , 57 ), but has two key superiorities: (i) the features used in our model are strongly supported by published studies and provide strong information about the key mechanisms of brain metastasis; and (ii) the primary locations of BMPs are not limited to one organ instead any organs, strongly suggesting that our predicted mechanism captures something fundamental.…”
Section: Resultsmentioning
confidence: 58%
“…These diseases are those in which ICIs are used more and for a longer time, being the first authorized therapeutic indications shared by the most used ICIs (3,39). In the same way, it should be considered that melanoma and lung cancer patients commonly present brain metastases such as secondary solid tumor (40)(41)(42). So, based on this, the reported brain metastases could also be considered possible therapeutic failure, which today, according to good pharmacovigilance practices (GVP), should be submitted as ICSR when there is at least an associated ADR (43).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that lung adenocarcinoma, breast cancer, and bladder cancer can significantly produce brain metastasis (13)(14)(15) and cause poor treatment outcomes and poor prognosis (12,14,16). A recent study showed that the gut microbiota can promote the development of glioma (22,24), especially with respect to cell proliferation and tumor invasiveness phenotypes (19)(20)(21).…”
Section: Glioblastomamentioning
confidence: 99%
“…Many studies have shown that metastasis is the most lethal development, especially brain metastasis. Many works have reported that lung adenocarcinoma, breast cancer, and bladder cancer can produce brain metastasis at a significant frequency (12)(13)(14)(15) and cause poor treatment outcomes and poor prognosis (12,14,16). Esophageal cancer can affect intestinal microorganisms (17,18) and indirectly promote the development of GBM, leading to a poor prognosis (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%